2008
DOI: 10.4102/koedoe.v50i1.128
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of the spiders (Arachnida, Araneae) of the Polokwane Nature Reserve, Limpopo Province, South Africa

Abstract: As part of the South African National Survey of Arachnida (SANSA), spiders were collected from all the field layers in the Polokwane Nature Reserve (Limpopo Province, South Africa) over a period of a year (2005)(2006) using four collecting methods. Six habitat types were sampled: Acacia tortillis open savanna; A. rehmanniana woodland, false grassland, riverine and sweet thorn thicket, granite outcrop; and Aloe marlothii thicket. A total of 13 821 spiders were collected (using sweep netting, tree beating, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In a survey of the Polokwane Nature Reserve by Dippenaar et al (2008), a similar proportion (35%) of unidentifiable spider species was found. Expertise for identification is usually limited to selected families and global experts may need to be consulted, which creates delays in obtaining data; in many cases even global expertise does not exist.…”
Section: Discussionmentioning
confidence: 78%
“…In a survey of the Polokwane Nature Reserve by Dippenaar et al (2008), a similar proportion (35%) of unidentifiable spider species was found. Expertise for identification is usually limited to selected families and global experts may need to be consulted, which creates delays in obtaining data; in many cases even global expertise does not exist.…”
Section: Discussionmentioning
confidence: 78%
“…Sixteen articles were located in the three journals searched. Nine (56 %) of these were classified as inventories only Dippenaar et al 2008;Haddad et al 2006;DippenaarSchoeman 2006;Dippenaar-Schoeman et al 2005;Haddad 2003;Dippenaar-Schoeman & Leroy 2003;Foord et al 2002), one (Wesolowska & Haddad 2009) included an inventory as well as other research, in this case systematics of the taxon. Six comprised other kinds of research.…”
Section: Resultsmentioning
confidence: 99%
“…Failing to do so can lead to tenuous conclusions about relative species richness, and hence the relative value of protected areas in conserving species. An example of such a comparison is presented in Dippenaar et al (2008). They found 275 spider species in the protected area they surveyed and stated that this was comparable with the 268 species found in another protected area within the same biome, without comparing species accumulation curves.…”
Section: Completeness Of Inventoriesmentioning
confidence: 94%
“…All these species are foliage dwellers, and the absence of diagnostic ground dwelling species are probably the result of the localised distribution of epigeal species within the Savanna Biome. A total of 10 published surveys of the Savanna Biome have been undertaken over the last 20 years (Dippenaar-Schoeman et al, 1989;Foord et al, 2002;Whitmore et al, 2002;Dippenaar-Schoeman & Leroy, 2003;Modiba et al, 2005;Haddad et al, 2006;Dippenaar et al, 2008;Foord et al, 2008;Dippenaar-Schoeman et al, 2009;Muelelwa et al, 2010). The savanna has been better sampled than the other biomes and predictably has the most records (Fig.…”
Section: The Savanna Largest and Most Diverse Biome Issues Of Scalementioning
confidence: 99%
“…Therefore, in addition to alpha diversity at a site, understanding the role of beta diversity and the scale at which assemblages respond to the environment are particularly important considerations for managing a particular taxon's diversity in this biome. The results from three concurrent semi-quantitative studies between May 2004 and March 2006 in Limpopo Province (Dippenaar et al, 2008;Foord et al, 2008;Muelelwa et al, 2010) provides a basis for evaluating the role of alpha vs. beta diversity in generating spider diversity at various scales. The degree of turnover between the spider assemblages of the 18 plant communities distributed over 4 sites was summarized by computing Bray-Curtis similarities and the Chao estimator of the Sørensen similarity index (Chao et al, 2005); the latter index includes the effect of undetected species.…”
Section: The Savanna Largest and Most Diverse Biome Issues Of Scalementioning
confidence: 99%